DAMPAK PEMIKIRAN TEOLOGIS SALAFIYYAH BAGI KEMASLAHATAN UMAT - Ayu Nisrina Indah Sari; Devia Anggarista Tasuhi Kusuma; Naufal Luthfi Alifa (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2021)
This article discusses the role of three Islamic theologians in the treasures of Islamic thought. The three figures are Ibn Taymiyyah, Ibn Jauziyah, and Abdul Wahab. All three have important contributions and have a strong influence on Muslims to this day. Moreover, along with the development of Islamic teachings, the Muslim community adheres to different theological schools. One of these schools is the Salafiyyah school. The three figures we discussed also fall into the category of this Salafiyyah school. In this research, we use a qualitative methodology based on an analysis of the Islamic literature review. First, we briefly describe the meaning of Salaf and Salafiyyah, then we briefly describe the biographies of three Salafiyyah figures or theologians and their thoughts on monotheism and its impact on the benefit of the people. Some of the results of this research include: the thoughts of Ibn Taimiyyah, Ibn Jauziyyah, and Abdul Wahab are based on three main principles: (1) prioritizing the revealed text over reason; (2) rejecting theological issues (kalam); and (3) strict adherence to the Koran, Hadith, and ijma'.